The information essence of politics - Victoria Willyamovna Ushnitskaya, Natalya Rinatovna Balynskaya, Venera Nikolayevna Аntonova,; Midyhatovna Votchel, Pavel Viktorovich Limarev, Yulia Anatolievna Limareva, Liliia; Vladimirovna Ereklintseva, Elena (Opción, 2019)
In the article, the authors discuss the specific characteristics of the information essence of political processes via a functional and interdisciplinary approach. As a result, there are several types of information influence political processes. The first is the event line replicated in mass media with a certain response to events that shape social conscience. The authors of the article have come to the conclusion that the new political elite should have the skills to work with such information, as only its deep layer can unite people into a kind of community that is able to effectively solve historical problems.